White matter microstructure and sleep-wake disturbances in individuals at ultra-high risk of psychosis - Rasmussen, Jesper Ø.; Nordholm, Dorte; Glenthøj, Louise B.; Jensen, Marie A.; Garde, Anne H.; Ragahava, Jayachandra M.; Jennum, Poul J.; Glenthøj, Birte Y.; Nordentoft, Merete; Baandrup, Lone; Ebdrup, Bjørn H.; Kristensen, Tina D. (Frontiers in Human Neuroscience, 2022)
Abstract Aim: White matter changes in individuals at ultra-high risk for psychosis (UHR) may be involved in the transition to psychosis. Sleep-wake disturbances commonly precede the first psychotic episode and predict development of psychosis. We examined associations between white matter microstructure and sleep-wake disturbances in UHR individuals compared to healthy controls (HC), as well as explored the confounding effect of medication, substance use, and level of psychopathology. Methods: Sixty-four UHR individuals and 35 HC underwent clinical interviews and diffusion weighted imaging. Group differences on global and callosal mean fractional anisotropy (FA) was tested using general linear modelling. Sleep-wake disturbances were evaluated using the subjective measures disturbed sleep index (DSI) and disturbed awakening index (AWI) from the Karolinska Sleep Questionnaire, supported by objective sleep measures from one-night actigraphy. The primary analyses comprised partial correlation analyses between global FA/callosal FA and sleep-wake measures. Secondary analyses investigated multivariate patterns of covariance between measures of sleep-wake disturbances and FA in 48 white matter regions of interest using partial least square correlations. Results: UHR individuals displayed lower global FA (F=14.56, p<0.001) and lower callosal FA (F=11.34, p=0.001) compared to HC. Subjective sleep-wake disturbances were significantly higher among the UHR individuals (DSI: F=27.59, p<0.001, AWI: F= 36.42, p<0.001). Lower callosal FA was correlated with increased wake after sleep onset (r=-0.34, p=0.011) and increased sleep fragmentation index (r=-0.31, p=0.019) in UHR individuals. Multivariate analyses identified a pattern of covariance in regional FA which were associated with DSI and AWI in UHR individuals (p=0.028), but not in HC. Substance use, sleep medication and antipsychotic medication did not significantly confound these associations. The association with objective sleep-wake measures was sustained when controlling for level of depressive and UHR symptoms, but symptom level confounded the covariation between FA and subjective sleep-wake measures in the multivariate analyses. Conclusion: Compromised callosal microstructure in UHR individuals was related to objectively observed disruptions in sleep-wake functioning. Lower FA in ventrally located regions was associated with subjectively measured sleep-wake disturbances and was partly explained by psychopathology. These findings call for further investigation of sleep disturbances as a potential treatment target.